2008
DOI: 10.1071/ea07197
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation strategies for greenhouse gas emissions from animal production systems: synergy between measuring and modelling at different scales

Abstract: Animal production systems are large and complex sources of greenhouse gases (GHG), especially nitrous oxide (N2O) and methane (CH4). Emissions from these systems are expected to rise over the coming decades due to the increasing global population and shifting diets, unless appropriate mitigation strategies are implemented. In this paper, we argue that the main constraints for such implementation are: (i) the complex and often poorly understood controls of GHG sources in animal production systems; (ii) the lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Balanced fertilization had the largest effects on N leaching losses and balancing plant‐available manure nutrients with other fertilizers to match crop requirements would decrease the amount of applied N and the N surplus. This measure had large synergistic effects, because NO 3 leaching (e.g., Schröder et al, 2007), NH 3 emission (e.g., Bussink, 1994), and N 2 O emission (e.g., Velthof et al, 1997; Van Groenigen et al, 2008) decrease when N input decreases. In most countries, the mean amount of plant‐available N applied to the soil was higher than the crop needs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Balanced fertilization had the largest effects on N leaching losses and balancing plant‐available manure nutrients with other fertilizers to match crop requirements would decrease the amount of applied N and the N surplus. This measure had large synergistic effects, because NO 3 leaching (e.g., Schröder et al, 2007), NH 3 emission (e.g., Bussink, 1994), and N 2 O emission (e.g., Velthof et al, 1997; Van Groenigen et al, 2008) decrease when N input decreases. In most countries, the mean amount of plant‐available N applied to the soil was higher than the crop needs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For most situations this is a reasonable assumption (e.g., Reijneveld, A., J. van Wensem, and O. Oenema. 2008.…”
Section: Input Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that under certain conditions there is a good relationship between soil mineral N surpluses and N 2 O emissions at the field level van Groenigen et al 2008). However, as N 2 O emissions in soil are controlled by the microbiallymediated processes of nitrification and denitrification, soil moisture content and temperature in the days following application will also have a bearing on the N 2 O emissions that occur after fertilizer N has been applied.…”
Section: Improved Timing Of Mineral Fertilizer N Applicationmentioning
confidence: 99%
“…Mitigation can be counteracted by trade offs (van Groenigen et al 2008). They illustrated this for reducing N-losses and found possible trade offs in methane emission from manure storage.…”
Section: Introductionmentioning
confidence: 99%